Comparison of the Laryngeal View during Tracheal Intubation Using Airtraq and Macintosh Laryngoscopes by Unskillful Anesthesiology Residents: A Clinical Study. (17th November 2011) - Ferrando, Carlos; Aguilar, Gerardo; Belda, F. Javier
Abstract : Background and Objective . The Airtraq laryngoscope (Prodol Meditec, Vizcaya, Spain) is a novel tracheal intubation device. Studies, performed until now, have compared the Airtraq with the Macintosh laryngoscope, concluding that it reduces the intubation times and increase the success rate at first intubation attempt, decreasing the Cormack-Lehane score. The aim of the study was to evaluate if, in unskillful anesthesiology residents during the laryngoscopy, the Airtraq compared with the Macintosh laryngoscope improves the laryngeal view, decreasing the Cormack-Lehane score. Methods . A prospective, randomized, crossed-over trial was carried out on 60 patients. Each one of the patients were intubated using both devices by unskillful (less than two hundred intubations with the Macintosh laryngoscope and 10 intubations using the Airtraq) anesthesiology residents. The Cormack-Lehane score, the success rate at first intubation attempt, and the laryngoscopy and intubation times were compared. Results . The Airtraq significantly decreased the Cormack-Lehane score (P = 0.04 ). On the other hand, there were no differences in times of laryngoscopy (P = 0.645 ; IC 95% 3.1, +4.8) and intubation (P = 0.62 ; C95%  −6.1, +10.0) between the two devices. No relevant complications were found during the maneuvers of intubation using both devices. Conclusions . The Airtraq is a useful laryngoscope in unskillful anesthesiology residents improving the laryngeal view and, therefore, facilitating the tracheal intubation.